Standard plating vs. cortical strut and plating for periprosthetic knee fractures: a multicentre experience - Paolo Pichierri; Marco Filipponi; Marco Giaracuni; Danilo Leonetti; Luigi Meccariello; Giuseppe Rollo; Enrico Maria Bonura; Gazi Huri; Mario Ronga; Christian Carulli; Michele Bisaccia; Francesco Traina (Medicinski glasnik, 2019)
Aim: Periprosthetic fracture after knee arthroplasty occurs more frequently in the supracondylar area of femur, especially after low energy trauma associated with torsional or compressive forces. Several techniques have been described for the treatment of displaced fractures. The aim of this study is the evaluation of the outcomes and bone healing of periprosthetic femoral fractures managed by standard plate fixation compared to plating with bone grafting. Methods: Thirty-six periprosthetic fractures around the knee were selected. Eighteen patients underwent standard plate and screws fixation while other eighteen were treated by plating associate with a cortical strut. Knee Society Score (KSS) and Short Form 12 (SF12) with the UNION SCORE (RUS) were used for the evaluation of results. Results: After a minimum follow-up of 12 months, the results showed a statistically significant difference in SF-12, KSS, and RUS in favour of plating associated to bone graft with respect to the plating alone; four cases of non-union were recorded in the group of patients treated by standard plating. Conclusions: Our experience once again demonstrated that plating and bone grafting may ensure a mechanical and biological support for the healing of periprosthetic fracture of the knee more than simple plating.
Keywords: arthroplasty; cortical strut allograft; femoral fracture; internal fixation; knee; locking plate; periprosthetic fracture